Development of LKPD Based on Canva App In Improving Ability Think Critical Students in Learning Social Studies Class V SD BK Maranatha - Kristianti, Novianti Lisa; Misnah; Bau Ratu (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aims to develop Canva-based Student Worksheets (LKPD) designed to improve the critical thinking skills of fifth-grade students in Social Studies instruction. Employing a Research and Development (R&D) methodology, the study follows the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. The research subjects comprised 20 fifth-grade students at SD BK Maranatha, Sigi Regency. Data collection instruments included expert validation sheets, critical thinking tests, and student response questionnaires. Expert validation results indicated that the LKPD was highly feasible, with an average score of 83.5%. Limited trials revealed a significant improvement in students' critical thinking abilities, with an N-Gain score of 0.73, categorized as moderate to high. Student responses showed a high level of interest, with a score of 83.92%. These findings suggest that the Canva-based LKPD is feasible, engaging, and effective for enhancing critical thinking in Social Studies learning.